The potential association between thiamin, hyperglycemia and chronic diseases - Alaei Shahmiri, Fariba (Curtin University, 2012)
Chronic diseases, such as cardiovascular disease and diabetes, are the leading causes of morbidity and mortality worldwide. Recent studies have shown that in addition to diabetes mellitus, non-diabetic degrees of fasting and postprandial hyperglycemia are also directly linked to accelerated risks of cardiovascular diseases. Thiamin is a water soluble vitamin playing a key regulatory role as a co-enzyme in metabolic pathways implicated in the glucose metabolism. There is some evidence that diabetic patients are prone to thiamin deficiency possibly because of an increased excretion of thiamin in the urine. However, there has been no published study to investigate thiamin status in individuals with pre-diabetic range of hyperglycemia. Given this gap, we undertook a cross-sectional study, evaluating blood thiamin concentration of subjects with impaired glucose regulation compared with healthy people.To examine the main objective of this study, data of 64 subjects (29 men and 35 women) were analysed. These subjects consisted of 39 normal healthy volunteers and 25 hyperglycemics with plasma glucose levels at pre-diabetic ranges (16 IGT, 9 IFG). The mean intake of thiamin in both groups as assessed by a validated semiquantitative food frequency questionnaire was 1.37±0.72 mg/day for normal subjects and 1.46±0.51 mg/day for those with hyperglycemia. These values exceeded the Australian RDI for thiamin. There was no significant difference in the levels of RBC thiamin in hyperglycemic subjects relative to those in the normoglycemic group (0.95±0.17 vs. 0.88±0.24 nmol/g Hb, p=0.22).The two groups were also evaluated for a range of risk factors for CVD, including arterial stiffness. Hyperglycemic subjects had higher levels of fasting DVP parameters (SI & RI), accompanied with tendencies toward blunted response to ingested glucose load relative to normoglycemic group. These results suggest that screening of individuals with hyperglycemia by using a Pulse Trace machine may be a means of recognising cardiovascular complications at early stages. Further research with a larger sample size is recommended to extend these interesting results.Hyperglycemia is known to induce a variety of biochemical alterations at the cellular level, resulting in a range of vascular and tissue damages. The mechanism of action of supplemental thiamin seems to involve the diversion of "excess" metabolic load (glycolytic intermediates) away from glycolysis and toward the reductive pentose pathway, a secondary pathway for glucose catabolism. Thiamin supplementation was also shown to improve cardiovascular risk factors in diabetic rats, suggesting the potential effects of thiamin in prevention of diabetic complications.To date there has been no published study to investigate these effects in individuals with pre-diabetic range of hyperglycemia (IGT). Therefore, our objective in the second study was to assess the chronic effect of high dose thiamin supplement (300 mg/d) on glucose tolerance and some cardiovascular risk factors in individuals with hyperglycemia at an early stage. In this intervention study with a double blind cross - over design, the hyperglycemic subjects (n=12) were randomly allocated into two groups to receive either placebo for 6 weeks followed by a 14-week washout period and then thiamin for 6 weeks; or thiamin for 6 weeks, a 14-week washout period and placebo for 6 weeks.The results of our intervention study showed that after 6 weeks of supplementation, RBC thiamin increased from 0.93 (±0.17) nmol/g Hb to 1.56 (±0.31) nmol/g Hb. In subjects receiving placebo, fasting plasma glucose increased significantly from baseline after six weeks (6.11±0.70 vs. 5.87±0.63 mmol/L, p=0.003). This significant change was accompanied with concomitant increases in fasting plasma insulin (7.67± 4.39 vs. 6.64± 3.45 μIU/mL, p=0.04), and HOMA score (2.10±1.32 vs. 1.75±1.01, p= 0.02). However in the supplement arm, there was no significant change in fasting plasma glucose (6.01±0.79 vs. 6.02±0.68 mmol/L, p=0.83), fasting insulin (7.46 ±4.67 vs. 7.36± 4.40 μIU/mL, p> 0.05) or HOMA score (2.05±1.51 vs. 2.00±1.32, p=0.75) determined at week 6 compared to baseline (week 0), indicating that supplementation with high dose thiamin may have prevented the natural progression of hyperglycemia toward diabetes mellitus in individuals with impaired glucose metabolism at early stages. We also found that high dose thiamin therapy can improve glucose tolerance (week 0: 9.89±2.50 vs. week 6: 8.78±2.20 mmol/L, p=0.004), and attenuate diastolic blood pressure (week 0: 71.42 ±7.41 vs. week 6: 79.2± 5.84 mm Hg, p=0.005) in patients with impaired glucose metabolism. The findings of the present study suggest that thiamin therapy may be effective in patients with hyperglycemia at early stages.Previous studies examining the potential effects of thiamin under hyperglycemic condition have mainly been limited to animals. The current clinical study suggests that thiamin supplementation may be beneficial in humans with pre-diabetic ranges of hyperglycemia. Further studies are required to confirm these results and investigate the impact of thiamin supplementation on insulin secretion.The findings of this research have the potential to inform food formulations and dietary recommendations for people who are at risk of developing diabetes mellitus, and may have a role in the prevention of hyperglycemic complications. The findings of this study serve as a base for further research investigating the effectiveness of different doses of thiamin on cardiovascular risk factors.